Evaluation of existing poultry development policy and way forward to its development in Bangladesh - M. A. Hashem (Journal of Agriculture, Food and Environment)
The study was conducted to evaluate present status and the gaps of the existing poultry policy and to recommend the output to the concerned policy makers of the Government of Bangladesh. Among the existing policies, poultry development policy was considered for investigation. Research gaps were addressed through publishes data, SWOT analyses, structured questionnairessurvey, FGDs (Focus Group Discussions) and Key Informant Interviews (KIIs). The study was carried out in seven divisions of Bangladesh namelyDhaka, Chittagong, Rajshahi, Khulna, Sylhet, Barisal and Rangpur. Total 177 representative samples (covering all stakeholders like farmers, dealers and distributors, parent stock/hatchery owners) were interviewed from selected seven divisions. Three FGDs and 50 KIIs were administered with different stakeholders. Descriptive statistics like percentage, mean, ranks, bar and pie chart were used for data analyses. Binary logistic regression and Z test were also used to identify the variables influencing the acts and policy. SPSS 20 software was used for data analyses. From the findings it reveals that the authority is not functioning properly due to lack of action plan and monitoring cell. Policy itself faulty in respect of filing case with DLS permission, terms of punishment, nature of bail, lack of magistracy power of DLS officials, lack of diagnosis of diseases, feed, medicine, drugs and livestock products analyses laboratory. Policy should be implemented on step by step basis targeting a period by 2020. Govt. should enforce action plan by implementing acts and policy considering organic and safe food showing zero tolerance to offenders. If policy is implemented ensured not only nutritional security, food safety and sustainable animal production but also livestock business and industry people will be benefitted and consumer will get safe food. Therefore, proper implementation of act and policies will ensure the development of poultry sector in Bangladesh.